Chronology of the Late Pleistocene archaeological sequence at Vanguard Cave, Gibraltar: Insights from quartz single and multiple grain luminescence dating. (20th January 2019) - Doerschner, Nina; Fitzsimmons, Kathryn E.; Blasco, Ruth; Finlayson, Geraldine; Rodríguez-Vidal, Joaquín; Rosell, Jordi; Hublin, Jean-Jacques; Finlayson, Clive
Abstract: Vanguard Cave is an archaeological site located on the shoreline of the Rock of Gibraltar at the south-western extreme of the Iberian Peninsula. It is part of a limestone cave system facing the adjacent Governor's Beach on the south-eastern coast of Gibraltar and has been filled to the roof with more than 17 m of sedimentary deposits. Due to its long stratified sequence, comprising rich palaeoenvironmental and faunal records as well as multiple Palaeolithic occupation layers, Vanguard Cave provides valuable information for our understanding of human behaviour and dispersal across south-eastern Iberia in general and particularly about the strategic role of the promontory of Gibraltar for past human populations. The development of a reliable absolute chronology for the sedimentary sequence at Vanguard Cave is therefore of great importance in this context. In this study, we applied optically-stimulated luminescence dating to sand-sized quartz grains from the uppermost ∼4 m of the Vanguard Cave deposits, as well as from the Hyaena Cave sediments – a small niche adjacent to the main cave chamber. We use single-grain and multiple-grain dating to clarify the depositional history of the sedimentary sequence, as well as to assess the reliability of the two dating approaches and their potential for future chronological studies at the site. The single-grain and multi-grain ages are consistent with one another and indicate no partial bleaching or post-depositional mixing of the sediments. Our results suggest that Vanguard Cave experienced continuous sediment accumulation probably since the last sea-level highstand in MIS 5, and was completely filled by ∼43 ka (MIS 3). The eastern side of the Rock of Gibraltar faced an exposed coastal shelf covered with savannah and an active coastal dune system during MIS 3. Our results indicate that similar environmental conditions are likely to have persisted also during MIS 4 and large parts of MIS 5.